O4-S1.04 Rapid spread of herpes simplex virus-2 in the human genital tract. (10th July 2011) - Schiffer, J; Swan, D; Magaret, A; Johnston, C; Selke, S; Wald, A; Corey, L
Abstract : Background: Genital herpes simplex virus-2 (HSV-2) infection consists of shedding episodes that correlate with transmission and genital lesion formation. Episodes are heterogeneous in terms of viral production and duration. Methods: Using quantitative PCR data from 14 685 daily genital swabs performed daily in 531 persons, we summarised 1020 episodes according to their frequency, duration, peak HSV DNA copy number, first and last swab copy number, expansion and decay slopes, and morphology. We designed competing dynamical stochastic mathematical models and attempted to fully reproduce result ranges for each of these episode features. The models assumed the possibility of concurrent, spatially distinct plaques of viral infection and immunologic response. Results: Our spatial model reproduced all kinetic features of the empirical shedding data. The model and parameter set that achieved best fit highlights three distinct mechanisms of viral spread. First, HSV-2 is constantly dispersed from neurons to epidermal cells throughout the genital tract at a rate of ∼100 HSV DNA copies/day. Approximately 75 times each year, a neuron-derived viral particle infects an epidermal cell, initiating an infectious plaque of epidermal cells and a detectable shedding episode. Second, within each plaque, cell-to-cell spread of HSV-2 particles occurs extremely rapidly between epidermal cells. One cell can produce 105 cell-associated HSV genomic copies/day, with 3% of viral particles infecting a neighbouring cell each day. In large plaques, >105 cells may be infected within ∼12 h producing up to 109 HSV DNA copies/ml. Third, cell-free viruses, despite being 3000-times less infectious than cell-associated viruses, decay more slowly and initiate spatially distinct secondary plaques. We use video simulations to display that episodes longer than 3 days, consist of dozens of concurrent viral plaques. Despite rapid cell-to-cell spread of HSV-2, infected cells are eliminated by localised CD8+ T-cells within 24 h of plaque initiation. Moreover, the extent of secondary plaque formation prior to episode termination is determined by spatial CD8+ T-cell density surrounding the site of infection. Conclusions: Genital HSV-2 utilises three kinetically distinct methods of spread to initiate and sustain prolonged shedding episodes. The extent and severity of secondary plaque formation is determined by spatial immune cell density.